Análise de metabólitos secundários produzidos por fungos endofíticos associados à Cupressus lusitanica - Amaral, Luciana da Silva (Universidade Federal de São Carlos, 2009)
Some phytopatogenic fungi found in Cupressus species produces phytotoxins very aggressive to the host plant. Surprisingly, these toxins are diterpenoids structures, as well as some endogenus metabolites in Cupressus species. This fungi ability appears to be a specialized strategy in the association fungi-plant. These observations motivated the development of the present work, which relates the isolation of microorganisms associated to the species Cupressus lusitanica, and to its study, aiming a correlation of the chemical profile among the organisms involved in this association. During two collects of plant material from an exemplar found in the campus of the UFSCar, five endophytic fungi had been isolated and called NICL1-5. A preliminary identification indicated that possibly four of them belong to the Xylaria genus, and one to the Guignardia genus (NICL4). The analysis with GC-MS had detected three isocoumarins (mellein, mellein methyl ether, 5- formylmellein), as well as an eremophilane sesquiterpene (valencene) in extracts of NICL3 fungi. From the extracts of the same fungi, had been obtained three eremophilanes sesquiterpenes (two news in literature) by the use of classical methodologies of chromatography. These compounds had been identified using a series of NMR data in 1D and 2D. From the study of the secondary metabolites of NICL5 had been obtained ergosterol, sorbitol and three cytochalasins (cytochalasin C, cytochalasin D and cytochalasin Q). The metabolism if NICL5 had also been studied, when free amino acids were added in the culture medium. By the analysis with HPLC-MS significant alterations in the NICL5 metabolism had been detected, as a possible induction of the biosynthesis of a new cytochalasin, from the amino acid tryptofane. The analysis of the plant material indicated the presence of biflavonoids and some diterpenes. However, these compounds had not been detected in fungi extracts, being identified only sesquiterpenes.
Analysis of secondary metabolites produced by endophytic fungi associated to Cupressus lusitanica
Keywords: Fungos endofíticos; Cupressus lusitanica; Sesquiterpenos eremofilanos; Citocalasinas; CIENCIAS EXATAS E DA TERRA::QUIMICA